Radio Frequency Based Wireless Battery Charging of Cellular Phones - Erwin Normanyo; Philip Blewushie; Cyril Yao Atatsi (Jurusan Teknik Elektro Universitas Andalas, 2022)
The challenge of regularly charging the battery of cellular phones has brought about new and more convenient ways to realising cellular battery charging. The wireless power platform has been explored for years bringing about many dimensions to its realisation. In this research, developed a wireless charging of Li-Ion battery of a cellular phone using commercial-off-the-shelf components vis-a-vis Radio Frequency (RF) energy. A MAX2623 voltage controlled oscillator was used to generate RF signals at a frequency of 915 MHz. Through a series of amplifier stages, the signal is radiated using a half-wave dipole antenna. The signal is received by a remote receiver module made up of 5 dBi gain half-wave dipole antenna which is impedance matched to a bridge rectifier made of SMS3929 Bridge Quad Schottky low turn-on voltage diodes. The rectified output is received by a EH4205 low voltage booster which amplifies the input into two paralleled MAX 682 charge pumps. The paralleled MAX 682 charge pump delivers a constant output voltage of 5 V DC and current of 500 mA. Within a 4 m radius the receiver module can receive enough power for the realisation of wireless battery charging.